Foldable and Recyclable Iontronic Cellulose Nanopaper for Low-Power Paper Electronics - Cunha, Inês (2022)
Nanomodelling and Nanofabrication – i3N, project CHIHC, reference PTDC/NAN‐MAT/32558/2017, project CELLECTIVE, reference PTDC/CTM‐CTM/4653/2021, The authors would also like to thank their colleagues Daniela Gomes, Ana Pimentel, Sónia Pereira and Tomás Calmeiro from CENIMAT/i3N for the SEM, DSC‐TGA, XRD and AFM measurements, respectively.